2012
DOI: 10.1534/genetics.112.143818
|View full text |Cite
|
Sign up to set email alerts
|

A Redundant Function for the N-Terminal Tail of Ndc80 in Kinetochore–Microtubule Interaction in Saccharomyces cerevisiae

Abstract: The N-terminal tail of Ndc80 is essential for kinetochore-microtubule binding in human cells but is not required for viability in yeast. We show that the yeast Ndc80 tail is required for timely mitotic progression and accurate chromosome segregation. The tail is essential when cells are limited for Dam1, demonstrating a redundant function for the Ndc80 and Dam1 complexes in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 21 publications
(34 reference statements)
3
23
0
Order By: Relevance
“…5 A). These results support the notion that, unlike in humans, deletion of the N terminus in yeast Ndc80 is tolerated because its absence is sufficiently balanced by Dam1 complex activity (Lampert et al, 2010; Demirel et al, 2012).…”
Section: Resultssupporting
confidence: 84%
“…5 A). These results support the notion that, unlike in humans, deletion of the N terminus in yeast Ndc80 is tolerated because its absence is sufficiently balanced by Dam1 complex activity (Lampert et al, 2010; Demirel et al, 2012).…”
Section: Resultssupporting
confidence: 84%
“…Mutants in the Dam1 phosphorylation sites lead to biorientation defects in vivo (Cheeseman et al 2002) and Aurora B phosphorylation site mutants in Ndc80 exhibit biorientation defects when Aurora B function is further compromised in vivo (Akiyoshi et al 2009a). These data suggest that Ndc80 phosphorylation is important but redundant with additional substrates in yeast (Akiyoshi et al 2009a;Demirel et al 2012).…”
Section: Kinetochore Biorientationmentioning
confidence: 88%
“…CH domains have diverse functions and have been identified in other microtubule binding proteins (Hayashi and Ikura 2003;Dougherty et al 2005). An unstructured N-terminal tail on Ndc80 enhances the microtubule binding activity of the complex (Wei et al 2005;DeLuca et al 2006;Wei et al 2007;Ciferri et al 2008;Miller et al 2008;Alushin et al 2010), although it is not essential for yeast viability due to redundancy with Dam1 (Kemmler et al 2009;Demirel et al 2012;Lampert et al 2013). The interaction between Ndc80 and microtubules is largely electrostatic and requires the C-terminal tails of tubulin ).…”
Section: Kmnmentioning
confidence: 99%
“…It is important to note that the absolute value of force is not as significant as the changes in tension reported by the Ndc80 FRET sensor for discovering and testing mechanistic models of force coupling between kinetochores and kMT plus‐ends. In budding yeast, the MT binding N‐terminal tail of Ndc80 is not essential . At metaphase, Suzuki et al found very low tension at metaphase through interphase in the Ndc80 tension sensor when the N‐terminal tail was deleted, although centromeres were stretched to their normal mean length of ∼800 nm at metaphase .…”
Section: The Fret Tension Sensor Within Budding Yeast Ndc80 Protein Rmentioning
confidence: 99%